Role of shape in substrate-induced plasmonic shift and mode uncovering on gold nanocrystals. Issue 40 (4th October 2016) - Qin, Feng; Cui, Ximin; Ruan, Qifeng; Lai, Yunhe; Wang, Jianfang; Ma, Hongge; Lin, Hai-Qing
Abstract : The substrate effect on the plasmonic properties of Au nanocrystals is strongly dependent on the nanocrystal shape. Abstract : A number of plasmonic devices and applications, such as chemical and biological sensors, plasmon-enhanced solar cells, optical nanoantennas, metamaterials and metasurfaces, require the deposition of plasmonic metal nanocrystals on various substrates. Because the localized plasmon resonance modes, energies and strengths are strongly dependent on the dielectric function of the surrounding environment, the substrate is expected to largely affect the plasmonic properties of supported metal nanocrystals. Therefore, understanding the effects of the substrate on the plasmonic properties of metal nanocrystals and the roles of the involved factors will be crucial for designing various plasmonic devices that are made of metal nanocrystals deposited on different substrates. Herein we report on our study and results of the effects of substrates with distinct dielectric functions on the plasmonic properties of three types of Au nanocrystals. A combination of experiments and numerical simulations shows that the presence of a substrate causes plasmonic shifts as well as the appearance of new plasmon modes. The plasmonic shifts and the emergence of new plasmon modes are found to be dependent on the particle shape of Au nanocrystals and in turn on the fractional particle surface area that is in contact with the supporting substrate. For Au nanospheres and nanorods, plasmonic shifts, less than 100 nm, are observed on the scattering spectra by changing the supporting substrate from indium tin oxide to silicon. In comparison, a giant spectral shift of more than 300 nm is obtained for Au nanoplates. Moreover, silicon substrates induce the emergence of an out-of-plane quadrupolar mode of Au nanoplates, which interacts with an out-of-plane octupolar mode to give rise to a distinct Fano resonance. The Fano resonance is found to become stronger as the thickness of Au nanoplates is decreased. These results are of great importance for understanding the plasmonic properties of noble metal nanocrystals supported on various substrates, and for designing novel plasmonic nanostructures with desired optical properties and functions.